Peran Organizational Citizenship Behaviour dalam Meningkatkan Kepuasan Kerja Karyawan : Studi Kasus di PT. Mitra Agung Sawita Sejati - Machiko, Machiko; Elvinawanty, Rianda; Viola, Viola; Ardila, Rizky Juliani; Akmal, Mukhaira El (Dinasti Research, 2025)
The study explores the connection between OCB (Organizational Citizenship Behavior) and job satisfaction among employees at PT. MASS, highlighting that employees with higher job satisfaction are more likely to exhibit proactive behaviors consistent with OCB. Using a quantitative research method, the analysis reveals a Pearson correlation value of 0.349 and a p-value of 0.000 (p<0.05), demonstrating a statistically significant relationship between job satisfaction and OCB. Additionally, the research indicates that 12.2% of job satisfaction can be explained by OCB, as shown by the coefficient of determination for this variable.